Phishing Attacks and Protection Against Them - Ivanov, Michael A.; Kliuchnikova, Bogdana V.; Chugunkov, Ilya V.; Plaksina, Anna M. (IEEE NW Russia Young Researchers in Electrical and Electronic Engineering Conference, 2021)
Phishing, ransomware and cryptojacking are the main threats to cyber security in recent years. We consider the stages of phishing attacks, examples of such attacks, specifically, attacks using ransomware, malicious PDF files, and banking trojans. The article describes the specifics of phishing emails. Advices on phishing protection are given.